Consensus or Conflict? China and Globalization in the 21st Century - Wang, Huiyao; Michie, Alistair; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This open access book brings together leading international scholars and policy-makers to explore the challenges and dilemmas of globalization and governance in an era increasingly defined by economic crises, widespread populism, retreating internationalism, and a looming cold war between the United States and China. It provides the diversity of views on those widely concerned topics such as global governance, climate change, global health, migration, S&T revolution, financial market, and sustainable development. .
Back to the future or a brave new world: Reflections on how the COVID-19 pandemic is reshaping globalization -- COVID-19 as a catalyst in the transition to a future of multipolar global cooperation -- Will liberal hegemony lead to a cold war in Asia -- Forging a partnership between the China and the world in an era of division: Finding common ground in climate change and health -- Challenges and reconstruction of the international order in the post COVID-19 era. .
Keywords: International relations; Globalization; International Relations; Globalization